Fostering Religious Tolerance in Catholic Religious Education: A Study of Policy Impact in Indonesia - Suswakara, Ignasius; Atasoge, Anselmus Dore Woho; Wahyuningrum, Paulina Maria Ekasari; Para, Eduardus Raja (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2024)
This study examines the levels of religious tolerance among students at six Catholic universities in Indonesia and the efforts to sustain and enhance this tolerance. Employing a mixed-method approach, specifically the Sequential Exploratory model, the research begins with the collection and analysis of quantitative data, followed by qualitative data. An online questionnaire completed by 250 students enrolled in Catholic Religious Education study programs reveals that students exhibit a very high level of tolerance (90%) in terms of acceptance, recognition, respect and cooperation. However, several areas require attention: the establishment of places of worship, representation of diverse religious backgrounds in public leadership roles, respect for religious observances and willingness to engage in activities with adherents of other religions. Interviews indicate that the six study programs have implemented policies promoting inter-religious tolerance in both academic and non-academic domains. Nonetheless, tolerance has not yet become a central focus in the policies of certain programs. This study highlights the need for higher education institutions to address these issues to further strengthen students’ tolerance, despite the already high levels observed.